"A study on the effect of Co, Cr and Ti on the corrosion of FE40AL intermetallic in molten NaCl–KCl mixture". (December 2015) - Romo, L.; Gonzalez-Rodriguez, J.G.; Porcayo-Calderon, J.; Guardian, R.; Salinas-Bravo, V.M.
Abstract: The effect of the addition of 3 at% Cr, Co or Ti on the corrosion behavior of Fe40Al intermetallic alloy in 1 M NaCl:1 M KCl mixture at 750 °C has been carried out by using electrochemical techniques. Techniques included potentiodynamic polarization curves, linear polarization resistance and electrochemical impedance spectroscopy measurements. It has been found that the addition of either Cr, Co or Ti decreased the corrosion rate of Fe40Al intermetallic by almost five times due to the formation of a passive layer, absent in the base alloy. This was because the diffusion of Al towards the top of the alloy for the establishment of a protective Al2 O3 layer was enhanced by the presence of these alloying elements. The corrosion rate for the base alloy was under diffusion control of the reactants, whereas that for alloyed intermetallic was under charge transfer control. Highlights: Fe40Al intermetallic was alloyed with 3% Cr, Co or Ti. They were corroded in 1 M NaCl-1M KCl at 750 °C. Electrochemical techniques including impedance spectroscopy measurements were taken. The addition of Cr, Co or Ti decreased the alloy corrosion rate. The formation of a passive Al2 O3 layer was found due to Al outwards diffusion.